2022
DOI: 10.3390/cancers14051106
|View full text |Cite
|
Sign up to set email alerts
|

RAB20 Promotes Proliferation via G2/M Phase through the Chk1/cdc25c/cdc2-cyclinB1 Pathway in Penile Squamous Cell Carcinoma

Abstract: RAB20, a member of the RAS GTPase oncogene family, is overexpressed in several cancers with poor outcomes, promoting tumorigenesis and inducing genomic instability. Here, we performed comprehensive genomic sequencing on eight penile squamous cell carcinoma (PSCC) and normal tissue pairs and found that RAB20 was upregulated in tumors, especially in metastatic lymph nodes. RAB20 overexpression in tumors was further verified by qPCR, Western blotting, and immunohistochemistry of our newly established PSCC cell li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For example, Lv S et al found that inhibiting CYCLINB1 resulted in suppressed proliferation, invasion, and epithelial mesenchymal transition of hepatocellular carcinoma cells and enhanced sensitivity to TRAIL-Induced apoptosis ( Lv et al, 2020 ). Also, CYCLINB1 is a defined biomarker in esophageal squamous cell carcinoma ( Li et al, 2023 ), penile squamous cell carcinoma ( Tan et al, 2022 ), gastric cancer ( Li et al, 2021 ), breast cancer ( Liu et al, 2019 ), nasopharyngeal carcinoma ( Xie et al, 2019 ), etc. As an important factor in so many cancers, our studies provided a new idea that TUBB may function in tumor formation by interacting with the CYCLINB1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lv S et al found that inhibiting CYCLINB1 resulted in suppressed proliferation, invasion, and epithelial mesenchymal transition of hepatocellular carcinoma cells and enhanced sensitivity to TRAIL-Induced apoptosis ( Lv et al, 2020 ). Also, CYCLINB1 is a defined biomarker in esophageal squamous cell carcinoma ( Li et al, 2023 ), penile squamous cell carcinoma ( Tan et al, 2022 ), gastric cancer ( Li et al, 2021 ), breast cancer ( Liu et al, 2019 ), nasopharyngeal carcinoma ( Xie et al, 2019 ), etc. As an important factor in so many cancers, our studies provided a new idea that TUBB may function in tumor formation by interacting with the CYCLINB1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, chemotherapy options and e cacy are limited in PSCC, and there is still a lack of available targeted therapies in clinical practice and relevant basic research [3,8]. Several studies have reported that RAB20 and IDO1 overexpression promote cell proliferation and induce immunosuppression in PSCC [12,21]. Other serum biomarkers, such as CXCL5, CXCL13 and CCL20, are associated with nodal metastasis in small cohorts [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance was read on a spectrophotometer at 450 nm for 7 consecutive days. In addition, wound healing assays and Matrigel Transwell invasion assays were used to evaluate the progressive capability of cells as described in our previous study [21].…”
Section: Cell Proliferation and Invasion Assaysmentioning
confidence: 99%
See 2 more Smart Citations